Menimbang Counter Legal Draft Kompilasi Hukum Islam - Husain Insawan (Institut Agama Islam Negeri (IAIN) Kendari, 2009)
Bolting of interpretation of emancipatory contemporary trodden on at “ freedom “ type of gender selected, the legal counter draft of Kompilation Punish Islam ( KHI ) designed. Learn from bleak past experience, likely movement especial influence of gender (This PUG) try to lift degree of womankind which during the time feel “to be harmed” by KHI. In consequence, there is some important point needing up di-blow nakedly by the compiler teams of [so that/to be] correct looked to be wanted by the picture is this movement. This matter at the same time give an opportunity to society to criticize, so that impress that legal counter of a draft of KHI this follows to be owned by process society. A point which is urgency peeped out the among others the problem of marriage ground, dowry, foundation, and marriage duration. Keyword: KHI, marriage ground, dowry, foundation, and marriage duration.